The intervention by an antimicrobial stewardship team can improve clinical and microbiological outcomes of resistant gram-negative bacteria. Issue 12 (December 2019) - Yamada, Koichi; Imoto, Waki; Yamairi, Kazushi; Shibata, Wataru; Namikawa, Hiroki; Yoshii, Naoko; Fujimoto, Hiroki; Nakaie, Kiyotaka; Okada, Yasuyo; Fujita, Akiko; Kawaguchi, Hiroshi; Shinoda, Yoshikatsu; et al.
Abstract: Antibiotic stewardship (AS) improves patient outcomes and rates of antibiotic susceptibilities. However, the long-term effect of AS programs (ASPs) on mortality is unclear. This study aimed to assess the impact of bedside interventions by an AS team (AST) on clinical and microbiological outcomes. This retrospective study enrolled patients with bloodstream infections (BSI) and long-term use of broad-spectrum antibiotics (more than 7 days). The main outcomes were 30-day and in-hospital mortality of patients with BSI. The secondary outcomes were the day of therapy (DOT) and susceptibility of antipseudomonal agents. Cases were classified into two groups: the pre-ASP group comprised cases between 2011 and 2013 and the post-ASP group, between 2014 and 2016. The outcomes were then compared between the two groups. Among the patients with all BSI (n = 1187), no significant differences in 30-day mortality were observed between those in the pre-ASP and post-ASP groups. However, in-hospital mortality was significantly lower in the post-ASP group than that in the pre-ASP group (24.8% vs. 18.0%; P = 0.004). Furthermore, the 30-day and in-hospital mortality of resistant gram-negative bacteraemia was significantly lower (20.4% vs.10.5%; P = 0.04 and 28.0% vs.16.1%; P = 0.03). The DOT of broad-spectrum antibiotics decreased except that of tazobactam/piperacillin. The susceptibilities of tazobactam/piperacillin, ceftazidime, cefepime, sulbactam/cefoperazone, gentamicin, ciprofloxacin levofloxacin, imipenem and meropenem were significantly better. Interventions by the AST can improve the clinical and microbiological outcomes, especially resistant gram-negative bacteria. Furthermore, this effect of our ASP can continue for a long term.